The Importance Of Business Research Skills In Entrepreneurial Orientation For Digital Transformation - Hamburg, Ileana (Advances in Social Sciences Research Journal, 2019)
In recent years area of entrepreneurship has gained significant attention nationally and internationally. It is one of the main skills priorities of national governments and EU council. Traditionally associated with commercial activity, entrepreneurship has gained traction as a key competence necessary to allow society as a whole to adapt to the changing economic climate. An important aspect particularly in the digital transformation is entrepreneurial orientation (EO) as the proactive nature of businesses of products and services in the market seeking for new innovations by even investing into it in spite of the high risk following it (Miller, 1993). It seems that organizations guided by a combination of market, technology, entrepreneurial learning (EL) and entrepreneurial orientation (EO) are well-positioned to take advantage of the opportunities presented by digital technologies. Small and medium sized companies (SMEs) greatly contribute to employment and wealth in Europe but there are limited studies into the specific skills needs required for SMEs into the future. Skills such as problem solving, critical thinking and entrepreneurship allow learners to adapt to changes, communication, digital skills and teamwork allow learners to collaborate and exploit technology in the changing workplace. Research is a key element of entrepreneurial success, but how these skills particularly workplace-oriented ones improve entrepreneurial orientation has not been widely explored in the literature. This paper explores the importance of EO and entrepreneurship today, the skills required to allow our society to become more entrepreneurial and identifies the potential of workplace research skills to develop entrepreneurial capacity in all facets of work, particularly within SMEs.